Activation of human α-carbonic anhydrase isoforms I, II, IV and VII with bis-histamine schiff bases and bis-spinaceamine substituted derivatives - Suleyman Akocak; Nabih Lolak; Silvia Bua; Alessio Nocentini; Claudiu T. Supuran (Taylor & Francis Group, 2019)
A series of histamine bis-Schiff bases and bis-spinaceamine derivatives were synthesised and investigated as activators of four human (h) carbonic anhydrase (CA, EC 4.2.1.1) isoforms, the cytosolic hCA I, II and VII, and the membrane-associated hCA IV. All isoforms were effectively activated by the new derivatives, with activation constants in the range of 4.73-10.2 µM for hCA I, 6.15-42.1 µM for hCA II, 2.37-32.7 µM for hCA IV and 32 nM-18.7 µM for hCA VII, respectively. The nature of the spacer between the two histamine/spinaceamine units of these molecules was the main contributor to the diverse activating efficacy, with a very different fine tuning for the diverse isoforms. As CA activators recently emerged as interesting agents for enhancing cognition, in the management of CA deficiencies, or for therapy memory and artificial tissues engineering, our compounds may be considered as candidates for such applications.